Interfaith Marriage Among Muslim Minorities: A Comparative Legal Analysis - Nur Solikin; Ahmad Nizar Mohammad Syamwil; Alvin Suadi; Afif Sabil; Mohammad Firmansyah (Indonesian Journal of Law and Islamic Law (IJLIL), 2025)
The purpose of this study is to determine the differences in opinion between Abdullah ibn Bayyah and Muhammad Yusri Ibrahim regarding interfaith marriage among Muslim minorities. This study uses normative legal research by adopting a comparative approach to identify the similarities and differences in the thinking of these two figures. The results of this study show that the differences in opinion between Abdullah ibn Bayyah and Muhammad Yusri Ibrahim regarding cases of interfaith marriage are influenced by their respective views, which combine several legal principles. In the case of “the validity of marriage if one of the spouses converts to Islam,” Yusri Ibrahim prefers the opinion of Ibn Qayyim as the main figure of the Hanbali school of thought, without considering Qaul al-Ṣahābī as an argument (hujjah). This differs from Ibn Bayyah, who uses Qaul al-Ṣahābī as an argument (hujjah) in accordance with the Maliki school of thought. Ibn Bayyah does not discuss the limits of taisīr (ease) in interfaith marriage issues at length. However, in terms of application, both figures agree on setting burdensome conditions. Ibn Bayyah prioritizes a deep discussion of maṣlaḥah (public interest), with various considerations, and explores more universal and facilitative concepts. Thus, his opinion is more flexible and easier to apply to cases of interfaith marriage in Singapore. Ibn Bayyah's opinion is based on considerations of the social reality of minority Muslims, so that his legal decisions are not textual and are more cautious. This differs from Yusri Ibrahim's opinion, which tends to be stricter and more difficult to apply in countries with non-Muslim majorities. This is because most of his opinion is very textual, following the foundations of Islamic law and his school of thought, without considering the public interest and the social realities of minority Muslims. The practical implications of this research have an impact on the legality of giving inheritance to wives or children who are not Muslim, and the right of a father to be the marriage guardian for his daughter, based on the opinion of Ibn Bayyah. This study suggests that the fiqh formulations of contemporary scholars on interfaith marriage can serve as a guideline for Muslim minorities in Western countries by taking social realities into account.